Comb-like hybrid plasmonic ring resonator for large and voltage tunable group delay - Mishra, Rahul Dev (2023)
A nanophotonic ring resonator based on hybrid plasmonic waveguide is numerically proposed. Introduction of a comb-like structure in the resonator results in large group delay which can be tuned electrically. The proposed silicon-based nanophotonic structure incorporates comb-like design with copper-Air subwavelength grating on SiO2 which supports resonance enhanced propagation of hybrid plasmonic mode confined in 50 nm thick SiO2. The device with its engineered design shows an ultra-large group delay of 208 ps for 1 mm length. The proposed device also exhibits a voltage tunable group delay with a tuning of 48 ps on varying the voltage from-5 V to 5 V. The proposed device with its CMOS compatible and scalable design is useful for integrated optoelectronic circuits. The reported large delay and wide tuning make it a perfect candidate for applications in optical delay lines, signal processing, beam steering in phase array antennas and in microwave photonics.